The Implementation of Quality Control and Quality Assurance in the Assurance and Control of Community Education Quality at Majlis Ta'lim Musala Al-Khatib Barokah - Sabda Nabil; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article aims to analyze the implementation of Quality Assurance (QA) and Quality Control (QC) in guaranteeing and controlling the quality of community education at Majlis Ta’lim Musala Al-Khatb Barokah. The study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of the study indicate that the implementation of QA is carried out through community needs-based program planning, setting learning material standards, and periodic evaluation of activity implementation. Meanwhile, the implementation of QC is realized through direct supervision of the learning process, monitoring congregation attendance, and assessing the quality of material delivery by teachers. However, the implementation of QA and QC still faces obstacles in the form of limited human resources, a less than optimal documentation system, and the absence of standard operating procedures. The discussion shows that these conditions have not yet contributed to improving the quality of community education, but still require strengthening in the aspect of quality management systematization to be more effective, measurable, and sustainable